HUBUNGAN POLA ASUH IBU DENGAN PERKEMBANGAN ANAK USIA 1- 3 TAHUN DI WILAYAH SLAWU KECAMATAN PATRANG - Armawati, Ni Made (FKM - UNEJ, 2012)
The Child development is the higher the ability of the structure and function of the body. One of factor that can be influenced of mother care. Based on justification on March 2011, for the 10 children district of Slawu, Patrang, 10% children happen an deviate, 20% children grown up with doubt, and 70% is normaly. This research to found an relationship of arrange of mother care with the grown up of the children 1-3 years old the district of Slawu, Patrang. The design of research is correlation analytic. Number of population were 60 respondents, and the sample was 52 respondents. The data collection use an likert and KPSP. The data was analysid by spearman rank. The result of mother care, 75% use an kind of autoratife care, 15,38% kind of permissive care, and 9,62% use kind of authority care. The grown up of the children that normal is 76,92%, 13,46% grown up of the children is doubt, 9,62% grown up of the children have an deviate after analyze the data with manual and computerization use an spearman rank technic. Can be conclude that Ha excepted, there is relationship between relationship of arrange of mother carewith the grown up of the children 1-3 years old the district of Slawu, Patrang.Based on the research hope to the mother is an mother care in autorative care, so the grown up of the children follow the rule with the age of the children. Keywords : Mother care, the grown up of the children.